Influence Of Organizational Citizenship Behavior To Employee Performance With Employee Competences And Job Satisfaction As Predictors - Andhi Supriyadi; Aurilia Triani Aryaningtyas (Faculty of Economics and Business Udayana University, 2022)
In the age of globalization where the midst of increasingly fierce competition, human ability as a resource for mastery of technology, adaptation and responsiveness to change is needed. This research is done to explore and analyze the impact of job satisfaction and competency on employee performance. Besides that organizational citizenship behavior is a mediating variable. Respondents used in this study were employees of the Garment Company factory in Semarang Regency as many as 105 people. The questionnaire method is used to collect the primary data needed. The AMOS SEM program is used for analytical tools. The results of the study found that: 1). Employee competency variables and job satisfaction variables have a positive influence on OCB. 2). Employee competency variables and job satisfaction variables have a positive influence on employee performance. 3). OCB has a positive influence on employee performance. 4). Employee competency variables and job satisfaction variables have a positive influence through OCB on employee performance.